African Political Philosophy: Theories of Power, Justice, and Governance (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
African political philosophy encompasses various conceptions of power, morality, justice, and governance, often prioritising communal harmony, balance, and reciprocity over individual interests. African political philosophy also addresses the legacies of colonialism and slavery, informing perspectives on justice, governance, and development. The study employed the critical analysis method. The study critically analyses African political discourses, including identity and unity, development, liberation, democracy, nation-building, and sovereignty. The study posits that cultural diversity, which acknowledges the blending of cultures, languages, and values, must serve as the foundation for African identity and unity. The article also critiques the modernisation model of development, advocating for a balanced approach that incorporates government intervention and control. The study concludes that African perspectives on justice, governance, and development are shaped by a thorough analysis of historical injustices. Africa needs to find a middle ground between embracing liberalism and implementing a controlled market economy in order to move forward. The continent must embrace the appropriate methodology, implement the correct economic ideology, and allow for necessary political interventions.